Status of individual indicators of cytokin profile in the early period of development of viral disease duration on the blood of experimental pneumonia - Furdychko, L. O.; Ohonovsky, R. Z. (Journal of Education, Health and Sport, 2017)
Today, current problems and pneumonia, gastric ulcers, which can be regarded as an independent disease or as a complication. In this paper we describe the contents of cytokines (CC) in the blood during the early period of experimental pneumonia disease and stomach ulcers. For the experiment, we selected two models of disease: experimental pneumonia (EP) and peptic ulcer (PU). Materials and methods. The study was conducted on 39 male guinea pigs, weighing 180 - 210 g test animals were divided into three groups. The experimental pneumonia caused by the method Shlyapnykova V. N., Solodova T. L., gastric ulcer simulated method Komarov V. I. All guinea pigs carried determine the concentration of cytokines: TNF-α, IL-6 and IL-10 in serum using ELISA (ELISA) using the kits of the company «Diaclone» (France), according to the enclosed instructions. Digital statistical results processed by using Student’s criterion. Results and discussion. In the study of the system EP and cytokines in VHSH found that in the test day of the experiment were as likely changes in the content of proinflammatory and antiinflammatory cytokines compared with the group of intact animals Results and discussion, CC proinflammatory IL-6 was found to increase its concentration to 61.1% (r≤0,05) on the fourth day, the eighth day of the disease models, this figure increased by 68.9% (r≤ 0.05) compared with kotrolem. A similar trend was observed from the following cytokines - TNF-α, which is typical of proinflammatory cytokines and other markers of generalized non-specific inflammation. There was increase in this indicator in fourth and eighth days of TNF-α respectively 59.4% (r≤0,05) and 65.6% (r≤0,05) relatively intact group of porpoises. Consequently, studies cytokine profile in serum under conditions established experimental models of diseases increase in the pool of inflammatory CC. Analysis of anti-inflammatory cytokine IL-10 for 4 days and VHSH EP showed its reduction by 22.5% (r≤0,05) when compared to the 1st group of animals experiment. Reduction of the Central Committee observed for 8 days at 31.4% (r≤0,05) compared with control animals. Thus, the study of cytokines (TNF-α, IL-6 and IL-10) showed increase in proinflammatory and anti-inflammatory interleukins decline, indicating that the balance between pro- and anti-inflammatory CC.